1969
DOI: 10.1139/e69-151
|View full text |Cite
|
Sign up to set email alerts
|

Ostracodes as Quaternary paleoecological indicators

Abstract: Quantitative and specific distribution of ostracodes are dependent on the physical and chemical limitations imposed by their environment, which in turn are controlled by geological, hydrological, botanical, and climatic factors. Once the nature of these controls has been defined for a region, the ecological limitation of specific ostracodes can be determined. Knowing the ostracode's tolerance limits then allows one to reconstruct the environments of the past, through paleoclimatic, paleoecologic, paleogeologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 1 publication
3
51
0
2
Order By: Relevance
“…A former high lake level of unknown age, suggesting a large lake, is also indicated by the presence of lake marl about 7 m above the modern level of Williams Lake (Seaburg, 1985). The presence of Cytherissa lacustris in Williams Lake sediments (Schwalb et al, 1995) indicates a deep, well oxygenated, cold-water lake such as those found today in boreal forests of northern Canada and Alaska (Delorme, 1969(Delorme, , 1970Danielopol et al, 1990). If there was a large lake, then Cytherissa lacustris also should have been found in Shingobee Lake sediments.…”
Section: Spruce Period (>98 Ka)mentioning
confidence: 96%
See 1 more Smart Citation
“…A former high lake level of unknown age, suggesting a large lake, is also indicated by the presence of lake marl about 7 m above the modern level of Williams Lake (Seaburg, 1985). The presence of Cytherissa lacustris in Williams Lake sediments (Schwalb et al, 1995) indicates a deep, well oxygenated, cold-water lake such as those found today in boreal forests of northern Canada and Alaska (Delorme, 1969(Delorme, , 1970Danielopol et al, 1990). If there was a large lake, then Cytherissa lacustris also should have been found in Shingobee Lake sediments.…”
Section: Spruce Period (>98 Ka)mentioning
confidence: 96%
“…Oxygen-isotope values may display positive offsets from equilibrium of about 2% (Xia et al, 1997a;von Grafenstein et al, 1999;Keatings, 2000). Ostracodes are also valuable environmental indicators that provide information about the physical and chemical properties of their environment (Delorme, 1969(Delorme, , 1970(Delorme, , 1991Forester et al, 1987;Smith, 1993). Additionally, oxygen and carbon isotopes from marl were analyzed to cover gaps in the ostracode record and to compare the isotopic signatures of surface waters where marl precipitates versus bottom waters at the sediment-water interface, where the analyzed ostracodes live.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the overwhelming taxonomic difficulties with the Chironomidae (Crisman, 1978), it is often impossible to distinguish among an ecologically diverse group of species within a genus, therefore complicating paleolimnological, and certainly paleoclimatological, reconstructions. We echo Delorme's (1969Delorme's ( , p. 1471 statement: "the amount of paleoecological information obtained by such interpretations is proportional to the amount of ecological data available on the particular organism or fauna1 assemblage." It is this dearth of precise, species-specific ecological data that 428 LETTERS TO THE EDITOR so severely constrains the utility of freshwater invertebrates in paleoecological interpretations.…”
mentioning
confidence: 74%
“…Total and relative abundances were recorded for the sediment samples. Based on Delorme (1969Delorme ( , 1989, values for the standard taphonomic variables of fragmentation, abrasion, disarticulation (carapace/valve [C/V] ratios), and adulthood (adult/juvenile [A/J] ratios) were recorded to establish the synecology (ecology of the communities) as opposed to the autoecology (ecology of single species) of the ecosystem (Adams et al, 2002). Autoecology, however, was used to integrate the environmental framework.…”
Section: Methodsmentioning
confidence: 99%
“…Their sensitivity to temperature makes ostracodes very useful for paleoclimate reconstructions (Cohen et al, 2000;Palacios-Fest, 2002). Once the ecological requirements of ostracodes are determined, it is possible to reconstruct paleoenvironments from the geologic record (Delorme, 1969;Palacios-Fest, 1994;Holmes and Chivas, 2002).…”
Section: Palacios-festmentioning
confidence: 99%